STABILIZATION OF ANODE MATERIALS FOR HIGH-PERFORMANCE ZINC-ION BATTERIES: THEORETICAL ANALYSIS AND CONCEPTUAL SOLUTION (Universal International Scientific Journal, 2026)
Zinc-ion batteries (ZIB) are promising energy storage systems due to their low cost, safety, and operation based on an aqueous electrolyte. However, dendrite formation and corrosion processes on the metallic zinc anode limit the cycle stability. In this work, the physicochemical mechanisms of dendrite growth are analyzed and a conceptual approach is proposed to smooth the ion flow using an artificial interface layer based on graphene. The proposed methodology requires experimental verification in the future
Keywords: zinc-ion batteries; dendrite; graphene